Educação integrada e direitos humanos: o caso do Ensino Médio Integrado do IFPB- Campus Guarabira. - Costa, Luiza Oliveira Nicolau da (2016)
This Master's Dissertation has its researching object the examining of the human rights education held in the context of a specific education, the integrated professional education to high school, in a delimited field, the Integrated Course of Computing at IFPB - Campus Guarabira. The research begins, at the first chapter, with the consideration of education’s role and the work in the context of the sociability capital and from it to understand the educational concept underlying the integrated project on current policies. Such educational design is structured around an emancipatory perspective for the working class and an articulated practice with the interests of the dominated class, by considering the work as an educational principle for the feasibility of an integral human formation. The analysis of such educational concept demonstrates the dialogue of its principles and foundations with complex view of human rights, which demands the approach of its discussion about the excluded ones and claims a pedagogical action for opening and guarantee spaces of struggle around the construction of the dignity and human emancipation. From this reading of human rights, fostered by Herrera Flores (2009), it is proposed that the work as an educational principle, within the integrated education, demands worker access to technical, scientific and cultural knowledge needed for a critical reading of socio-productive relations, as well as needed human rights knowledge to open spaces of debate and struggle that will enable the effective construction worker dignity in times of crisis. To better support the theoretical and empirical way proposed in this study, its promoted in the second chapter, a brief historical background of Brazilian education, demonstrating the mishaps drawn around the educational duality of high school, split between workup education and vocational education which brought forth, from the struggles for its overcoming, the germs that today subsidize the integrated educational concept assumed by Brazilian official documents. Furthermore, it is proposed, in the third chapter, a description of education in human rights from international and national documents that provide the current framework of the matter. The work culminates, in the fourth chapter, with the appropriation of analysis from the documents and the voices of the subjects related to the search field, demonstrating the (re)meanings that are operated in the field about the integrated concepts of education and human rights education. The field research proposed in this study is intended, therefore, to recover the analytical categories mentioned in the first chapter and the debate proposed by them, using them as a parameter for the analysis of (re)constructed meanings in the research field.